SPEAKING ACCURACY, FLUENCY, AND BEYOND: INDONESIAN VOCATIONAL STUDENTS’ VOICES - Cendra, Anastasia Nelladia; Sulindra, Eric (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
Speaking mastery has been known as the benchmark of language learning, yet many students still find it difficult to speak with great accuracy and fluency. To widen the knowledge and fill the gaps in the existing research, this present qualitative-descriptive research is to investigate how vocational students see accuracy, fluency, and other psychological-related aspects in speaking as well as collecting some suggestions to create a better speaking class. By distributing questionnaires and conducting semi-structured interviews, the present research revealed that the participants were slightly more inclined towards accuracy compared to fluency, which may result in the inhibition of risk-taking. Moreover, some psychological-related challenges such as feeling nervous, unconfident, and afraid to make mistakes were prevalent among the participants which affected their speaking performance negatively. Finally, the participants yielded some suggestions for a better speaking class, which include assisting students in four stages of speaking and providing appropriate feedback.